2009
DOI: 10.1248/cpb.57.177
|View full text |Cite
|
Sign up to set email alerts
|

Acylated-Oxypregnane Glycosides from the Roots of Asclepias syriaca

Abstract: 177Asclepias syriaca L. is a plant indigenous to North America and distributed widely. The monarch butterfly (Danaus plexippus L.) feeds on the Asclepias genus for protection from vertebrate predators. 1) Asclepias species are known to contain many kinds of cardenolides and their glycosides. 2-9)A. syriaca has also been reported to contain these compounds. [10][11][12] We have previously studied cardenolides and their glycosides.13) But, until now, there have been no reports about pregnane glycosides from A. s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 29 publications
1
8
1
Order By: Relevance
“…[1][2][3][4][5][6][7][8] In the preceding paper, we reported on 8,12;8,20-diepoxy-8,14-secopregnane glycosides from the aerial parts of Asclepias tuberosa L.9) A. tuberosa L. is a plant indigenous to North America and distributed widely. Its roots are known as "pleurisy root" and used to treat pleurisy and bronchitis.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] In the preceding paper, we reported on 8,12;8,20-diepoxy-8,14-secopregnane glycosides from the aerial parts of Asclepias tuberosa L.9) A. tuberosa L. is a plant indigenous to North America and distributed widely. Its roots are known as "pleurisy root" and used to treat pleurisy and bronchitis.…”
mentioning
confidence: 99%
“…In addition, the benzoylisolineolon-related oxypregnane glyco- [22][23][24]. It was also reported that the C-1 of the inner cymaropyranose unit is characteristically resonating up-field around 95.0-95.9 ppm when linked to C-3 of the aglycone in contrast to C-1 of a terminal cymaropyranose (97.8-100.4 ppm) when linked to a sugar unit [14].…”
Section: Resultsmentioning
confidence: 99%
“…5-5.8 Hz) together with C-17 chemical shift at 56. 2-59.5 ppm [13,[17][18][19][20], while the b-configured H-17 resonates at d H 3.42-3.55 (J = 9.5 Hz) with 60.1-60.7 ppm for C-17 [16,[21][22][23].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 17α configuration was also confirmed by the observation that the carbonyl carbon of an α-linked methyl ketone at C-17 appears at δ 209.2, 209.3 and 214.5 ppm for the aglycones 6 , 7 and 8 , respectively, and at 214.4 ppm for the steroidal glycoside 3 , when compared with δ 217 ppm for the β configuration (Table 1). 17-Epimers having an α-oriented side chain were isolated from the twigs of Pergularia pallida (Khare et al 1984), the roots of Cynanchum wilfordii Hemsley (Tsukamoto et al 1985), the roots of Calotropis gigantea Dryand (Shibuya et al 1992), the roots of Cynanchum caudatum M. (Warashina and Noro 1995), the aerial part of Asclepias incarnata L. (Warashina and Noro 2000), the roots of Cynanchum auriculatum Royle ex Wight (Xhang et al 2000), the aerial parts of Cynanchum aphyllum L. (Kanchanapoom et al 2002), the stem of Marsdenia tenacissima (Deng et al 2005), and from the pericarps, hairy seeds and leaves of Solenostemma argel Hayne (Perrone et al 2008), the roots of Asclepias curassavica L. (Warashina and Noro 2008), the roots of Asclepias syriaca L. (Warashina and Noro 2009) (all of which species belong to the Asclepiadaceae family), and from Nerium oleander (Bai et al 2007) . …”
Section: Discussionmentioning
confidence: 99%